The new Greek/English interlinear New Testament : a new interlinear translation of the Greek New Testament, United Bible Societies' fifth revised edition with The New Revised Standard Version, New Testament (Tyndale House Publishers, 2020)
"The New Greek/English Interlinear New Testament contains a literal word-for-word English rendering of the Greek text in interlinear form. A parallel column of the New Revised Standard Version (NRSV) accompanies the interlinear text. Numerous textual notes are also included. The New Greek/English Interlinear New Testament is the newest interlinear translation that uses the UBS4/NA27 text"--